ICT and special educational needs: analysis of ICT skills teachers - Inmaculada Tello Díaz-Maroto; Antonia Cascales Martínez (RIED: Revista Iberoamericana de Educación a Distancia, 2015)
Today, we must consider the initial training of teachers with ICT, and continued learning, both of them essential for teachers for the quality of their educational work. In the field of ICT applied to education, technical training and pedagogical training are both necessary. We must accompany the accessibility of these resources with their educational use. ICT opens a new way to access information and offers a great communication bridge for contact and learning. However, for teachers to make use of these tools effectively they must first know the procedure, so they must be one of the main actors involved in the process of teaching and learning. Therefore, they should be updated in the proper use of ICT. To check the level of ICT training of teachers in service, we have used a questionnaire focusing on several dimensions related to ICT in the classroom: knowledge of these resources, teaching methodology, resource selection, evaluation and training received. The study sample consists of 147 teachers from 4 Spanish regions and 9 provinces. The sample used has been a purposive sampling, selecting teachers who have attended a training course on the use of ICT. The results show several differences in understanding the use of ICT in the Spanish territory and a high demand for specific training adapted to the reality of each center.